Ventricular arrhythmias originating from the basal septum of the ventricle: Clinical and electrophysiological characteristics and a systematic ablation approach - Shi, Linsheng; Wang, Cheng; Chen, Hongwu; Yang, Gang; Gu, Kai; Li, Mingfang; Chu, Ming; Liu, Hailei; Wang, Zidun; Ju, Weizhu; Chen, Minglong (Frontiers in Cardiovascular Medicine, 2022)
Background There is a paucity of data about VAs clustered at the vicinity of the basal septum of the ventricle. We aimed to report and characterize the clinical and electrophysiological features of basal septum VAs and explore the systematic ablation approach. Methods A consecutive series of 51 patients who had their VAs successfully ablated at the basal septum of the ventricle was enrolled in this study. The basal septum was defined as the area 2 cm away from the septal annulus, the upper boundary was the site of the left or right His-Purkinje system, and the lower boundary was the borderline that separated away from the septum. RFCA was performed based on detailed activation mapping or pace mapping. Patients who underwent VA ablation from other areas of the tricuspid annulus (TA) and mitral annulus (MA) during the same period were enrolled as the control group. Results The patients with basal septum VAs were significantly older (p < 0.01) and had more comorbidities (hypertension and coronary artery disease) (p < 0.01). Meanwhile, the precordial R wave transition was significantly different in right side, left side and intramural foci group (p < 0.001). Acute procedural success was achieved in 44 patients (86.3%) in the study group and in 63 patients (95.5%) in the control group. After a median of 12 (6–36) months of follow-up, compared with VA recurrence in the control group (2 cases), 11 patients with basal septum VAs had recurrences (p = 0.002), while a delayed cure was observed in 3 in intramural foci group. Conclusion Based on the unique anatomical and electrophysiological characteristics, a systematic approach for VAs originating from the basal septal area is warranted. Moreover, the follow-up data seemed to show a relative high recurrence rate for basal septal VAs during a period of time.